Volatility of returns and financial liberalization:new evidence - Tamat Sarmidi,; Norlida Hanim Mohd Salleh,; Siong , Hook law (Penerbit Universiti Kebangsaan Malaysia, 2012)
The main objective of this paper is to paper is to reinvestigate the relationship between liberalization and returns volatility by considering different level of economic fundamentals and level of openness. The real impact of financial liberalization is expected to vary across countries with different macroeconomic fundamentals and level of liberalization. This study is different from previous studies becouse we do not impose priori linear restriction on the estimation. Employing endogenous threshold estimation methods, our finding shows that the relationship between liberazation and returns volatility is nonlinear and the negative impact of liberalization can be annulled for countries with strong and stable government.